A qualitative enquiry into the meaning and experiences of wellbeing among young people living with and without HIV in KwaZulu-Natal, South Africa. (August 2020) - Govindasamy, Darshini; Ferrari, Giulia; Maruping, Kealeboga; Bodzo, Paidamoyo; Mathews, Catherine; Seeley, Janet
Abstract: Young people in sub-Saharan Africa encounter health and livelihood challenges which may compromise their wellbeing. Understanding how young people's wellbeing is defined could strengthen wellbeing policies. We investigated perceptions and experiences of young people's wellbeing, and whether these aligned with Ryff's psychological wellbeing (PWB) model. Data were collected between January–August 2018 through focus-group discussions (n = 12) and in-depth interviews (n = 16) with young people living with and without HIV, selected purposively from South African healthcare facilities. Key informant interviews (n = 14) were conducted with healthcare workers and subject-matter experts. Using a framework approach, we situated our analysis around dimensions of Ryff's PWB model: autonomy, self-acceptance, purpose in life, environmental mastery, positive relationships, personal growth. Young people's wellbeing was rooted in family and peer relationships. Acceptance and belongingness received from these networks fostered social integration. HIV-related stigma, crime and violence reduced their perceived control and social trust. For males, fulfilling gendered roles made them feel socially valued. Self-perceived failure to uphold sexual norms undermined women's social contribution and autonomy. Social integration and contribution framed young people's wellbeing. However, these dimensions were not fully captured by Ryff's PWB model. Models that consider relationality across socio-ecological levels may be relevant for understanding young people's wellbeing. Highlights: Young people's wellbeing in peri-urban South Africa is cultivated within social networks. Family and peer relationships promote social contribution and integration, key dimensions of young people's wellbeing. A social wellbeing model may be more appropriate for capturing the totality of young people's wellbeing in this setting.